2007
DOI: 10.1118/1.2779944
|View full text |Cite
|
Sign up to set email alerts
|

Off‐axis dose response characteristics of an amorphous silicon electronic portal imaging device

Abstract: Amorphous silicon (a-Si) electronic portal imaging devices (EPIDs) have typically been calibrated to dose at central axis (CAX). Division of acquired images by the flood-field (FF) image that corrects for pixel sensitivity variation as well as open field energy-dependent off-axis response variation should result in a flat EPID response over the entire matrix for the same field size. While the beam profile can be reintroduced to the image by an additional correction matrix, the CAX EPID response to dose calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Dosimetry using EPIDs or portal dosimetry has received considerable attention recently due to its relatively high-resolution of 0.392mm amorphous silicon (a-Si) flat-panel detector [15][16][17][18]. Several authors have extensively studied the dosimetric properties of a-Si 500 and a-Si 1000 EPID and its application in IMRT [19][20][21][22][23][24][25]. Varian has recently released a-Si 1200 portal imager with larger area, high resolution of 0.336 mm and improved backscatter for dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Dosimetry using EPIDs or portal dosimetry has received considerable attention recently due to its relatively high-resolution of 0.392mm amorphous silicon (a-Si) flat-panel detector [15][16][17][18]. Several authors have extensively studied the dosimetric properties of a-Si 500 and a-Si 1000 EPID and its application in IMRT [19][20][21][22][23][24][25]. Varian has recently released a-Si 1200 portal imager with larger area, high resolution of 0.336 mm and improved backscatter for dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, amorphous silicon (a-Si)-based EPIDs have been developed with excellent image quality [17] and requirements for dosimetric purposes [3,7,8,10,12,13,15]. So far only a few reports have addressed dosimetric applications for this type of detector from Elekta [14,18,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that an amorphous silicon, indirect detection EPID responds much more efficiently at off-axis distances than within the central 10 cm of the detector. 6 Furthermore, it has also been demonstrated that off-axis EPID response is much higher than the dose response of an ion chamber in water at similar off-axis distances. 7,8 Consequently, a common method of EPID calibration utilizes dark field and flood field ͑FF͒ corrections, which effectively flatten the response across the entire surface of the EPID.…”
Section: Introductionmentioning
confidence: 99%